Macroscopic, Histologic, and Immunomodulatory Response of Limb Wounds Following Intravenous Allogeneic Cord Blood-Derived Multipotent Mesenchymal Stromal Cell Therapy in Horses - Suzanne J. K. Mund (MDPI AG, 2021)
Limb wounds are common in horses and often develop complications. Intravenous multipotent mesenchymal stromal cell (MSC) therapy is promising but has risks associated with intravenous administration and unknown potential to improve cutaneous wound healing. The objectives were to determine the clinical safety of administering large numbers of allogeneic cord blood-derived MSCs intravenously, and if therapy causes clinically adverse reactions, accelerates wound closure, improves histologic healing, and alters mRNA expression of common wound cytokines. Wounds were created on the metacarpus of 12 horses. Treatment horses were administered 1.51–2.46 × 108 cells suspended in 50% HypoThermosol FRS, and control horses were administered 50% HypoThermosol FRS alone. Epithelialization, contraction, and wound closure rates were determined using planimetric analysis. Wounds were biopsied and evaluated for histologic healing characteristics and cytokine mRNA expression. Days until wound closure was also determined. The results indicate that 3/6 of treatment horses and 1/6 of control horses experienced minor transient reactions. Treatment did not accelerate wound closure or improve histologic healing. Treatment decreased wound size and decreased all measured cytokines except transforming growth factor-β3. MSC intravenous therapy has the potential to decrease limb wound size; however, further work is needed to understand the clinical relevance of adverse reactions.